2012
DOI: 10.1038/nrc3184
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cells: an evolving concept

Abstract: The cancer stem cell (CSC) concept derives from the fact that cancers are dysregulated tissue clones whose continued propagation is vested in a biologically distinct subset of cells that are typically rare. This idea is not new, but has recently gained prominence because of advances in defining normal tissue hierarchies, a greater appreciation of the multistep nature of oncogenesis and improved methods to propagate primary human cancers in immunodeficient mice. As a result we have obtained new insights into wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
837
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,061 publications
(857 citation statements)
references
References 167 publications
14
837
0
6
Order By: Relevance
“…However, as yet, in no instance has a profile been identified that can reliably replace functional assays for normal stem cells. It should also be noted that many of the phenotypic markers found to be empirically useful for isolating particular subsets of cells in unperturbed normal tissue have proved to be functionally dispensable or differently regulated when they are activated in vivo or in vitro 3,4 . In addition, there is increasing evidence that normal tissue stem cells that are identified by their tissue-regenerative activity in different assays may fail to include cells with similar latent potentialities that are only revealed under different conditions.…”
Section: Csc Definitions and Terminologymentioning
confidence: 99%
See 3 more Smart Citations
“…However, as yet, in no instance has a profile been identified that can reliably replace functional assays for normal stem cells. It should also be noted that many of the phenotypic markers found to be empirically useful for isolating particular subsets of cells in unperturbed normal tissue have proved to be functionally dispensable or differently regulated when they are activated in vivo or in vitro 3,4 . In addition, there is increasing evidence that normal tissue stem cells that are identified by their tissue-regenerative activity in different assays may fail to include cells with similar latent potentialities that are only revealed under different conditions.…”
Section: Csc Definitions and Terminologymentioning
confidence: 99%
“…Not surprisingly, what is meant by the term CSC has evolved over that period. Historically, it first invoked the concept that malignant cell populations are organized as unidirectional cellular hierarchies in which CSCs constitute biologically unique subsets of cells, which are distinguished from the bulk of the cells that they produce by their exclusive ability to perpetuate the growth of a malignant cell population indefinitely [1][2][3][4] . This concept is of considerable clinical importance because it emphasizes the crucial need to target CSCs to achieve cures.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of tumor-propagating cells in the pathogenesis of cancer is becoming increasingly well recognized 1 . However, there are only a few reports supporting the existence of such cells in human lymphoma cell lines or in transgenic lymphoma mouse models 2– 5 .…”
Section: Introductionmentioning
confidence: 99%